2016
DOI: 10.3390/v8100286
|View full text |Cite
|
Sign up to set email alerts
|

Maporal Hantavirus Causes Mild Pathology in Deer Mice (Peromyscus maniculatus)

Abstract: Rodent-borne hantaviruses can cause two human diseases with many pathological similarities: hantavirus cardiopulmonary syndrome (HCPS) in the western hemisphere and hemorrhagic fever with renal syndrome in the eastern hemisphere. Each virus is hosted by specific reservoir species without conspicuous disease. HCPS-causing hantaviruses require animal biosafety level-4 (ABSL-4) containment, which substantially limits experimental research of interactions between the viruses and their reservoir hosts. Maporal viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Perhaps the best studied virus/reservoir host systems are the rodent-borne hantaviruses, which are similar to arenaviruses, in which the viruses establish apathogenic infections without eliciting aggressive immune responses [ 20 , 21 ]. In each of these systems, the viruses do not cause meaningful pathology and persist for many months or longer, and heterologous hantavirus inoculation of a reservoir host species also results in innocuous infections [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the best studied virus/reservoir host systems are the rodent-borne hantaviruses, which are similar to arenaviruses, in which the viruses establish apathogenic infections without eliciting aggressive immune responses [ 20 , 21 ]. In each of these systems, the viruses do not cause meaningful pathology and persist for many months or longer, and heterologous hantavirus inoculation of a reservoir host species also results in innocuous infections [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other experiments were dedicated to the analyzing of hantavirus infection in heterologous reservoir species. As such, McGuire et al [54] have shown that Maporal virus (MAPV), a South American hantavirus whose reservoir is the delicate pigmy rice ( Oligoryzomys delicates ), was able to infect deer mice in laboratory conditions. Similarly, de Souza et al [55] have revealed experimentally that Rio Mamore virus (RIOMV), another south American hantavirus naturally infecting Oligoryzomys microtis , was able to infect other Sigmodontinae rodents ( Necromys lasiurus and Akodon sp.…”
Section: Hantavirus Transmission: Modes Dynamics and Spill-overmentioning
confidence: 99%
“…Along this same line, some experiments have been designed to investigate whether hantavirus infections lead to similar or different responses in heterologous reservoir species compared to their natural reservoir. Cross-infections of deer mice have been conducted with ANDV and MAPV, with SNV infections being the reference model [53,54]. Some responses of deer mice were similar, regardless of the hantavirus used.…”
Section: Immune Mechanisms Behind the Biology Of Reservoir/hantavimentioning
confidence: 99%
“…The answer to this question is likely complicated and will vary between species of bats and species of viruses. In rodent reservoirs of pathogenic hantaviruses, in which the viruses establish persistent infection without meaningful pathology (18)(19)(20)(21)(22), the immune response is slow to develop (21) and is mediated by Fox-p3 + , TGFβ-expressing regulatory T (Treg) cells, which counter inflammatory disease (23,24) but at the expense of sterilizing immunity. Do bats have Treg cells?…”
mentioning
confidence: 99%